2009
DOI: 10.1007/s12032-009-9366-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of circulating matrix metalloproteinase-7 (MMP-7), CC chemokine ligand 18 (CCL18) and CC chemokine ligand 11 (CCL11) as markers for diagnosis of epithelial ovarian cancer

Abstract: Ovarian cancer remains a highly lethal disease. The aim of the present study was to evaluate the usefulness of measuring serum matrix metalloproteinase-7 (MMP-7), CC chemokine ligand 18 (CCL18) and CC chemokine ligand 11 (CCL11) in comparison with serum cancer antigen 125 (CA 125) for diagnosis of epithelial ovarian cancer (EOC). This study included 51 patients with EOC, 27 patients with benign ovarian lesions and 29 healthy volunteers. Serum CA 125 was determined by microparticle enzyme immunoassay, while ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 34 publications
(42 reference statements)
3
38
0
4
Order By: Relevance
“…However, the role of CCL18 in cancer progression is controversial. CCC18 was reported to participate in immunosuppression of ovarian cancer [39], but was also associated with prolonged survival in patients with gastric cancer [40]. Cytokine profile analysis of breast tumor-associated macrophages showed that CCL18 is abundantly expressed and promotes migration and invasion of breast cancer cells by enhancing their adherence to extracellular matrix; the CCL18 level in blood or cancer stroma was found to be associated with metastasis of patients with breast cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of CCL18 in cancer progression is controversial. CCC18 was reported to participate in immunosuppression of ovarian cancer [39], but was also associated with prolonged survival in patients with gastric cancer [40]. Cytokine profile analysis of breast tumor-associated macrophages showed that CCL18 is abundantly expressed and promotes migration and invasion of breast cancer cells by enhancing their adherence to extracellular matrix; the CCL18 level in blood or cancer stroma was found to be associated with metastasis of patients with breast cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of metastasis, it is vital for tumor cell to arrest in mediums, regulated by series of stimulus or inhibitors in the microenvironment. CCL18 triggers integrin clustering and ECM adherence of tumor cells, which eventually contribute to enhanced invasion and metastasis (Zohny & Fayed, 2010;Narita et al, 2011). Essentially, CCL18 could specifically bind to PITPNM3, stimulate calcium signaling and induce directional migration.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, CCL18 could specifically bind to PITPNM3, stimulate calcium signaling and induce directional migration. As the functional receptor of CCL18, PITPNM3 could be phosghorylated and then trigger a series of actions, such as activation of praline-rich tyrosine kinase (Pyk2), a key component of focal adhesion complex (FAC) (Lev et al, 1999;Zohny & Fayed, 2010). In our study, we chose MDA-MB-231 cells, a breast cancer line with metastasis potential.…”
Section: Discussionmentioning
confidence: 99%
“…Роль ММП-7 в диагностике РЯ оценили также F. Zohny и соавт [31]. В их работе определен уровень ММП-7 в сыворотке крови совместно с опухолевым маркером СА-125, который уже показал свою диагно-стическую и прогностическую значимость.…”
unclassified
“…Zohny и соавт. приводят аналогичные данные: исследователи не выявили достоверной разницы сы-вороточных уровней ММП-7 при различной распро-страненности процесса, степени дифференцировки опухолевых клеток и гистологических типах РЯ [31].…”
unclassified